Rare bird documentation form for Northern Goshawk at Volga River Recreation Area, 1981 - Myers, Robert K.et al (1981)
Rare bird documentation form for a Northern Goshawk at Volga River Recreation Area in Fayette County, IA on December 12, 1981. Epson - sheet feed